Comparison of Clinical Symptoms of Assumed vs. Actual Uterine Fibroids – Symptoms Described by Patients and Ultrasound Findings - Knudsen, Nina Isabelle; Wernecke, Klaus-D.; Kentenich, Heribert; David, Matthias (Geburtshilfe und Frauenheilkunde, 2020)
Purpose How many women assume that they have fibroids but are found not to have fibroids on ultrasound examination? How severe are the physical symptoms reported by these women compared to the symptoms reported by women with actual uterine fibroids? Are the symptoms more severe if the patient believes that she has at least one relatively large (dominant) fibroid or more than 3 fibroids?Material and Methods A total of 1548 patients completed an anonymous questionnaire in which they were asked about the number of their fibroids, dysmenorrhea and premenstrual symptoms, dyspareunia and bleeding disorders (using a numerical analog scale between 0 – 10). The questionnaire was administered in a hospital-based fibroid clinic. The information provided by the patients was then compared with transvaginal or abdominal ultrasound findings. The symptoms reported by women with and without fibroid(s) were compared.Results 1045 out of 1548 patients fulfilled the studyʼs inclusion criteria. Contrary to the information they provided, no fibroid(s) were detected in 6% (62 of 1045 patients) of patients on ultrasound examination. Of these women, 87% had dysmenorrhea, 79% had premenstrual pain and 57% reported dyspareunia. The severity of the symptoms was found not to be associated with the assumed size or number of fibroid(s). There was no significant difference in the pain reported by women without and by women with fibroids. Reporting a feeling of strong pressure on the bladder (OR: 1.18) or abdomen (OR: 1.12) or constipation (OR: 1.16) increased the likelihood of detecting a fibroid on ultrasound investigation.Conclusions The presence of manifest symptoms (dysmenorrhea, dyspareunia, premenstrual pain, bleeding disorders) does not allow conclusions to be made about the number or size of fibroids or about which therapy is indicated. Even an erroneous assumption about the presence of fibroids may result in patients experiencing symptoms.Fragestellung Wie viele Frauen nehmen Myome bei sich an, haben aber im Ergebnis der ärztlich-sonografischen Untersuchung keine Myome? In welcher Stärke treten Beschwerden bei diesen Frauen im Vergleich zu Myompatientinnen trotzdem auf? Sind diese Beschwerden stärker ausgeprägt, wenn die Patientin glaubte, dass sie mindestens ein relativ großes (dominantes) Myom oder über 3 Myome hat?Material und Methodik 1548 Patientinnen beantworteten einen anonymen Fragebogen mit Angabe ihrer Myomanzahl, Dysmenorrhö und prämenstruellen Beschwerden, Schmerzen beim Geschlechtsverkehr sowie Blutungsstörungen (numerische Analogskala 0 – 10) in einer Klinik-Myomsprechstunde. Anschließend erfolgte eine Gegenüberstellung der Patientinnenangaben mit dem transvaginalen bzw. ggf. abdominellen Ultraschallbefund. Die Beschwerdeangaben von Frauen mit und ohne Myom(en) wurden verglichen.Ergebnisse 1045 von 1548 Patientinnen entsprachen den Einschlusskriterien. Bei 6% (62 der 1045 Patientinnen) ließ sich entgegen ihren Angaben in der durchgeführten sonografischen Untersuchung kein Myom feststellen. Von diesen Frauen hatten 87% Dysmenorrhö, 79% prämenstruelle Schmerzen und 57% Dyspareunie. Die Beschwerdeausprägung zeigte keinen Zusammenhang mit der angenommenen Myomgröße oder -anzahl. Es zeigte sich kein signifikanter Unterschied in den Schmerzangaben von den befragten Frauen ohne und mit Myom(en). Die Angabe von starkem Druckgefühl auf die Blase (OR 1,18) oder im Unterbauch (OR 1,12) bzw. Obstipation (OR 1,16) erhöhten die Wahrscheinlichkeit, dass sonografisch ein Myom nachgewiesen werden konnte.Schlussfolgerungen Durch die Symptomausprägung (Dysmenorrhö, Dyspareunie, prämenstruelle Schmerzen, Blutungsstörungen) kann nicht auf die Anzahl oder die Größe von Myomen geschlossen oder eine Therapie abgeleitet werden. Bereits die Fehlannahme von Myomen kann bei Patientinnen zu Symptomen führen.
Keywords: fibroids; sonography; dysmenorrhea; dyspareunia; premenstrual pain